2014
DOI: 10.1021/cs501567x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbohydrates on the Hydrodeoxygenation of Lignin-Derived Phenolic Compounds

Abstract: Simulating lignocellulose-derived pyrolysis oil, the effects of carbohydrate derivatives on the hydrodeoxygenation of lignin-derived phenolic compounds, guaiacol in this study, were observed using supported ruthenium catalysts. Among several carbohydrate derivatives which possibly exist in the pyrolysis oil, the addition of furfural and 5-hydroxy­methylfurfural (5-HMF) significantly decreased the conversion of guaiacol, with density functional theory (DFT) calculations indicating that guaiacol competes with fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 32 publications
0
39
0
2
Order By: Relevance
“…Recently,t he influence of carbohydrate derivatives on catalyst performance was shown for the HDO of guaiacol catalysed by Ru/C, [209] as furfural and 5-hydroxymethylfurfural (5-HMF) strongly inhibited activity.A t2 70 8 8Ca nd under 40 bar pressure of H 2 ,f ull conversion of guaiacol was observed after 1h,r educing to just 30 %i nt he presence of equimolar furfural. Supporting DFT calculations of the Ru(0001) surface highlighted that furfural and 5-HMF bind more strongly than guaiacol.…”
Section: Prevention Of Recondensation In Lignin Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,t he influence of carbohydrate derivatives on catalyst performance was shown for the HDO of guaiacol catalysed by Ru/C, [209] as furfural and 5-hydroxymethylfurfural (5-HMF) strongly inhibited activity.A t2 70 8 8Ca nd under 40 bar pressure of H 2 ,f ull conversion of guaiacol was observed after 1h,r educing to just 30 %i nt he presence of equimolar furfural. Supporting DFT calculations of the Ru(0001) surface highlighted that furfural and 5-HMF bind more strongly than guaiacol.…”
Section: Prevention Of Recondensation In Lignin Oilsmentioning
confidence: 99%
“…As ac ase in point, it was recently shown that the presence of carbohydrates in the feed exerts an egative impact on the HDO reaction of guaiacol, taken as am odel compound for lignin-derived phenolics over Ru/C catalysts. [209] In conclusion, although modification of the already highly optimised Kraft process is conceivable,i ti si mportant to consider that, at least at present, high-quality cellulose fibres remain as the primary target because of their value (Kraft pulp global prices at 600-800 US$/ton as of January 2016). [210] Accordingly,aproductive line of investigation would be to devise an optimised system for maximising both the cellulose pulp quality and the quality of lignin (i.e., improving its susceptibility towards mild downstream valorisation), rather than exclusively focusing on the development of improved catalysts for treatment of highly-condensed Kraft lignins.I n fact, most technologies for (reactive) lignocellulose fragmentation have been developed with maximisation of the potential of the cellulosic fibres in mind, with lignin considered mainly as ab y-product, or worse,a saw aste.H owever, there is ag rowing recognition that if future pulp and paper industry operations are to be commercially successful, valorisation also of the lignin fraction is mandatory.…”
mentioning
confidence: 99%
“…The goal of the present study was to elucidate the effects of water on the HDO of lignin‐derived phenolic compounds, guaiacol in this study, as we previously observed the effects of carbohydrates 18. Simulating the biphasic nature of thermochemically prepared bio‐oils, a mixture of n ‐decane and water was used as a reaction medium for the hydrodeoxygenation of guaiacol.…”
Section: Introductionmentioning
confidence: 99%
“…Außerdem ist die Entfernung löslicher Kohlenhydrate wünschenswert, um Probleme bei der nachgeschalteten Behandlung zu vermeiden. Als typisches Beispiel wurde kürzlich aufgezeigt, dass sich das Vorhandensein von Kohlenhydraten im Einsatzmaterial negativ auf die über Ru/C‐Katalysatoren durchgeführte Hydrodesoxygenierung von Guajacol, als Modellverbindung für von Lignin abgeleitete Phenole, auswirkt …”
Section: Vorgeschaltete Behandlungunclassified
“…Kürzlich wurde der Einfluss von Kohlenhydrat‐Derivaten auf die Katalysatorleistung bei der Hydrodesoxygenierung (HDO) von Guajacol mit einem Ru/C‐Katalysator gezeigt . Durch Furfural und 5‐Hydroxymethylfurfural (5‐HMF) wurde die Katalysatoraktivität stark verringert.…”
Section: Nachgeschaltete Katalytische Behandlung Von Isoliertem Ligninunclassified